The Characteristics Of Phonetic Reasoning In The Arbitrator And The Great Ocean (Journal of the College of Basic Education, 2024)
The scholars did not only mention the phonetic phenomena that occur on the words without resorting to their interpretation and analysis and trying to remove the thumb from them, hoping to create a solid foundation to be followed in Arabic, with the rooting of rules and building assets through research in the Arabic arts extracted from the extension of reasoning and its tools Arabic was characterized by the multiplicity of formats associated with the contexts and affected by the multiplicity of dialects and the diversity of poetic novels, this led to the departure of its rules sometimes from the ordinary and stipulated, and as a result we followed in our research this ( As a result, we traced in this research (the characteristics of phonetic reasoning in the arbitrator and the great ocean) the pretexts that explain the reason for the departure from the phonetic rules, and what ibn saedoh referred to reasoned and quoted from others while highlighting the trends of phonetic reasoning and the evidence of protest adopted